Grade 6 Research Process Instruction: An Observation Study - Asselin, Marlene (Alberta Journal of Educational Research, 2001)
Current literacy standards include students' abilities to conduct research as an inquiry process and to gather, evaluate, and synthesize information from multiple sources. Observation data from 19 grade 6 classrooms were analyzed to describe research process instruction. Results showed that most of the teachers used traditional approaches to research tasks, monitored and supported students' procedural work through research projects, and that students used reference and textbooks far more than trade books and other types of texts. Findings suggest that students acquire topic-driven conceptions of the research process, encounter limited points of view about their research topic, and lack sufficient instruction on the cognitive processes of research. Implications for teacher educators and teacher-librarians are offered.